Raúl Castro and Cuba : a military story - Klepak, H. P. (Studies of the Americas., 2012)
This book tells the story of the military life of the longest serving minister of defense of any country in recent times. While the picture that often emerges of Raul Castro is that of a colorless younger brother of Fidela product essentially of that grander figure₇this book analyzes Raul Castro as a man of his own, a politician and an impressive military commander and organizer, as well as a highly original thinker on both military matters and wider national issues that have faced the Cuban state over more than half a century. Filling a gap in recent scholarship, it demonstrates that the government he has put into place in Cuba in the last four years is very much his, and is not, as some believe, a mere shadow of his brother's.